2014
DOI: 10.1016/j.neulet.2014.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide schizophrenia variant at MIR137 does not impact white matter microstructure in healthy participants

Abstract: A single nucleotide polymorphism (SNP rs1625579) within the micro-RNA 137 (MIR137) gene recently achieved strong genome-wide association with schizophrenia (SZ). However, the mechanisms by which SZ risk may be mediated by this variant are unknown. As miRNAs have the potential to influence oligodendrocyte development, we investigated whether this SNP was associated with variability in white matter (WM) microstructure. Diffusion tensor imaging (DTI) was conducted on 123 healthy participants genotyped for rs16255… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 35 publications
2
11
0
Order By: Relevance
“…A bioinformatics analysis of predicted and validated miR-137 target genes revealed a significant enrichment of these genes within the axonal guidance canonical pathway [1]. One target, ZNF804A , is a well-known schizophrenia candidate gene [25] that has been linked to reduced integrity of the corpus callosum [26], although its relationship to white matter integrity has varied across studies [27; 28]. Since many other miR-137 target genes are also schizophrenia risk genes [1], the role of these genes in white matter development and morphology lends support to our finding of MIR137HGrv genotype-by-diagnosis—rather than just genotype—effects on corpus callosum volume.…”
Section: Discussionmentioning
confidence: 99%
“…A bioinformatics analysis of predicted and validated miR-137 target genes revealed a significant enrichment of these genes within the axonal guidance canonical pathway [1]. One target, ZNF804A , is a well-known schizophrenia candidate gene [25] that has been linked to reduced integrity of the corpus callosum [26], although its relationship to white matter integrity has varied across studies [27; 28]. Since many other miR-137 target genes are also schizophrenia risk genes [1], the role of these genes in white matter development and morphology lends support to our finding of MIR137HGrv genotype-by-diagnosis—rather than just genotype—effects on corpus callosum volume.…”
Section: Discussionmentioning
confidence: 99%
“… 4 , 5 In line with the proposed influence of microRNA-137 (miR-137) on proliferation, migration and maturation of neural cells, 6 , 7 , 8 mechanisms important to the cognitive process, one of three intronic variants in high LD identified in this region (rs1625579) has been associated with a number of cognitively relevant phenotypes. These include lower performance in verbal episodic memory and vigilant attention, 9 altered fronto-amygdala connectivity during a face processing task 10 and decreased white matter integrity, 11 , 12 although a number of other studies have reported conflicting findings, with no effects of the MIR137 risk allele 13 , 14 on brain structure.…”
Section: Introductionmentioning
confidence: 99%
“…Lett et al (2013) also reported that North American schizophrenia patients carrying the TT genotype of this variant have reduced brain white matter density, diminished hippocampal volume, and increased lateral ventricle volume. However, other studies have not supported an association between miR-137 rs1625579 and schizophrenia or white matter microstructure (Kelly et al, 2014;Rose et al, 2014;Wang et al, 2014). Therefore, no consistent conclusion has been reached regarding the effect of this SNP on schizophrenia.…”
Section: Introductionmentioning
confidence: 91%